On Long-Distance Agree - Boeckx, Cedric (IBERIA: An International Journal of Theoretical Linguistics, 2010)
The present work examines the empirical reach of the minimalist operation Agree responsible for feature-licensing. I focus on patterns of so-called long-distance agreement and show that although not all instances of long-distance agreement that have been identified in the literature are unambiguous instances of ‘pure’ Agree (at a distance), at least some are. For these, an operation like Agree appears empirically necessary.